Microstructure and magnetism of austenitic steels in relation to chemical composition, severe plastic deformation, and solution annealing - Kamila Hrabovská; Ondřej Životský; Petra Váňová; Yvonna Jirásková; Lucie Gembalová; Ondřej Hilšer (Scientific Reports)
Abstract Three types of commercial austenitic stainless steels, 1.4307 (AISI 304 L), 1.4404 (AISI 316 L) 1.4845 (AISI 310 S) with different chemical compositions, are subjected to severe plastic deformation at room temperature by a unique Dual Rolling Equal Channel Extrusion (DRECE) method. Its impact is evaluated from the viewpoint of microstructure analyses, X-ray diffraction, and macroscopic magnetic properties completed by microscopic Mössbauer characteristics. The study also includes the solution annealing at 950 °C for 0.5 h to follow the recovering austenitic structure and paramagnetic state of steels with the aim to offer more information with respect to new technical applications. The results show the importance of the steel’s chemical composition and microstructure, mainly grain size, on the stability of the austenitic structure closely associated with the paramagnetic behaviour.